Duloxetine ameliorates the impairment of diffuse noxious inhibitory control in rat models of peripheral neuropathic pain and knee osteoarthritis pain. (11th June 2020) - Yoneda, Sosuke; Kasai, Erika; Matsuo, Midori; Tamano, Ryuta; Sakurai, Yusuke; Asaki, Toshiyuki; Fujita, Masahide
Highlights: Forepaw injection of capsaicin produces a DNIC response in the hindpaw of rats. DNIC response is reduced in rat chronic pain models. Duloxetine, but not pregabalin and celecoxib, ameliorates the impairment of DNIC. Abstract: Diffuse noxious inhibitory control (DNIC) is a phenomenon to reflect descending pain modulation in animals. Conditioned pain modulation (CPM) is the human counterpart of DNIC and is reduced in patients with several chronic pain conditions. Duloxetine is a serotonin and noradrenaline reuptake inhibitor that ameliorates CPM impairment in patients with diabetic neuropathy. Although some studies have reported the effects of different pharmacological agents on CPM, few studies have compared the effects of some analgesics in both humans and rodents. Therefore, we established a stable evaluation method for DNIC in rats and determined whether duloxetine and other specific analgesics affect DNIC impairment in rat models of peripheral neuropathic pain and osteoarthritis pain, two types of chronic pain. As a conditioning stimulus, capsaicin was injected into the forepaw of rats. The paw withdrawal threshold (PWT) in response to mechanical pressure was measured for the hindpaw. Peripheral neuropathic pain and osteoarthritis pain models were developed by partial sciatic nerve ligation (PSNL) and the intra-articular injection of 2 mg monoiodoacetate (MIA), respectively. Capsaicin (30–100 μg/site) increased the PWT, in a dose-dependent manner, in naive rats. The threshold significantly increased at 30 μg and reached its maximal level at 100 μg. The change in PWT following capsaicin injection was significantly reduced in PSNL-treated rats, but the threshold was increased by the subcutaneous administration of duloxetine (10 mg/kg). The oral administrations of pregabalin (10 mg/kg) and celecoxib (3 mg/kg) did not affect the PWT in PSNL-treated rats. Similarly, MIA-injected rats also showed a reduced change in PWT following capsaicin injection. Duloxetine, but not pregabalin and celecoxib, significantly increased the PWT in MIA-injected rats. These results suggested that duloxetine can directly ameliorate DNIC impairment in rat models of chronic pain. Duloxetine may be useful for modulating chronic pain by restoring function to the endogenous, descending, inhibitory pathway.